Prevalence of chikungunya virus infection in Sabah, Malaysia during 2017–2020 - Mya Myat Ngwe Tun; Jecelyn Leaslie John; Thanh Vu Nguyen; Maurine Mumo Mutua; Abdul Marsudi Manah; Yuki Takamatsu; Takeshi Urano; Kouichi Morita; Kamruddin Ahmed (BioMed Central Ltd., 2025)
Background Chikungunya virus (CHIKV) is a mosquito-borne alphavirus and an emerging global health threat. Most research on CHIKV in Malaysia has primarily focused on Peninsular Malaysia, with limited data on its distribution in the endemic regions of Borneo, particularly Sabah. This study aimed to determine the prevalence of CHIKV infection in Sabah, Malaysia. Methods A total of 130 serum samples, comprising 74 from febrile patients and 56 healthy individuals were collected between 2017 and 2018. Subsequently, 188 serum samples were obtained from febrile patients in Sabah, Malaysia during 2019–2020. All samples underwent quantitative real-time reverse transcription polymerase chain reaction (RT-qPCR) for the detection of the CHIKV genome. Additionally, serological tests were conducted to identify anti-CHIKV IgM and IgG antibodies. Serologically positive samples were further validated using neutralization assays to confirm the presence of CHIKV-specific antibodies. Results In 2017–2018, 16 out of 130 samples (12.3%) tested positive for recent CHIKV infections based on CHIKV RT-qPCR or anti-CHIKV IgM results, while in 2019–2020, 7 out of 188 samples (3.7%) showed recent infections. Among the 16 recent CHIKV-positive cases in 2017–2018, four were asymptomatic individuals. In 2017–2018, 24 (18.4%) individuals tested positive for anti-CHIKV IgG, with 15 (11.5%) showing positive neutralization test results. In 2019– 2020, 20 (10.6%) febrile patients were seropositive for anti-CHIKV IgG, with 17 (9.0%) showing CHIKV neutralization positivity. The CHIKV infection rate in Sabah was higher during 2017–2018 compared to 2019–2020. Conclusions To the best of our knowledge, this is the first report confirming the presence of CHIKV in both patients and healthy individuals in Sabah using RT-qPCR and neutralization tests. Although the likelihood of transmission from asymptomatic individuals is low, they still present a considerable public health risk. Our results indicate that both basic scientists and clinicians should consider CHIKV when diagnosing febrile patients, and policymakers should put in place effective surveillance and control measures. Keywords CHIKV, Real time PCR, Neutralization test, Sabah